(untitled) (Bangladesh Rice Journal, 2014)
Two on-farm experiments were conducted during dry seasons, 2001-04 at Kurigram and Pirgonj in Thakurgaon districts to select the best water management practices and to find out the suitable and economically viable combination of irrigation scheduling and fertilizer dose for maximizing irrigated rice yield. In alternate irrigation at saturation (AIS) treatment, about 28% water was saved compared to continuous flooding (CF), but it was needed to apply water frequently. However, alternate wetting and drying (AWD) method saved 31% and 39% water in Kurigram and Pirgonj, respectively compared to CF. In both the sites, there was no significant yield difference among the water treatments, though the applied water varied from 836-1046 mm in Kurigram and 802-1092 mm in Pirgonj. The water productivity in Kurigram ranged from 0.62 to 0.89 kg m-3, whereas in Pirgonj it varied from 0.54 to 0.75 kg m-3. Besides, AWD had the highest water productivity irrespective of locations and farmer can follow AWD practices for achieving competitive rice yield with reduced irrigation cost. The soil test based (STB) fertilizer management gave the highest grain yield followed by BRRI recommend dose irrespective of water managements. About 33-35% less amount of water was required in AWD compared to farmers practice (FP) in both the sites having 0.5-1.0 t ha-1 yield advantage. In both the locations, the water productivity was the highest with STB fertilizer in combination with AWD water management which required additional fertilizer cost of Tk. 2800 ha-1, but resulted in added benefit of Tk. 8400 ha-1 compared to FP. In STB fertilizer treatment, nutrient uptake was more compared to BRRI recommendation and FP. It was concluded from the study that AWD water management practice was the best option for water saving and improving water productivity. The combination of AWD with STB fertilizer management is suitable for maximum return from rice cultivation in light textured soils. DOI: http://dx.doi.org/10.3329/brj.v17i1-2.20902 Bangladesh Rice j. 2013, 17(1&2): 64-74